Complete response of renal cell carcinoma vena cava tumor thrombus to neoadjuvant immunotherapy. Issue 1 (11th March 2019) - Labbate, Craig; Hatogai, Ken; Werntz, Ryan; Stadler, Walter M.; Steinberg, Gary D.; Eggener, Scott; Sweis, Randy F.
Abstract : Background: Clinically localized renal cell carcinoma is treated primarily with surgery followed by observation or adjuvant sunitinib in selected high-risk patients. The checkpoint inhibitor immunotherapeutic agents nivolumab and ipilimumab have recently shown a survival benefit in the first-line metastatic setting. To date, there have been no reports on the response of localized renal cancer to modern immunotherapy. We report a remarkable response of an advanced tumor thrombus to combined immunotherapy which facilitated curative-intent resection of the non-responding primary renal tumor. We characterized the tumor microenvironment within the responding and non-responding tumors. Case presentation: A 54-year-old female was diagnosed with a locally advanced clear cell renal cell carcinoma with a level IV tumor thrombus of the vena cava. She was initially deemed unfit for surgical resection due to poor performance status. She underwent neoadjuvant immunotherapy with nivolumab and ipilimumab with a complete response of the vena cava and renal vein tumor thrombus, but had stable disease within her renal mass. She underwent complete surgical resection with negative margins and remains disease-free longer than 1 year after her diagnosis with no further systemic therapy. Notably, pathologic analysis showed a complete response within the vena cava and renal vein, but substantial viable cancer remained in the kidney. Multichannel immunofluorescence was performed and showed marked infiltration of immune cells including CD8 + T cells and Batf3 + dendritic cells in the thrombus, while the residual renal tumor showed a non-T cell-inflamed phenotype. Conclusions: Preoperative immunotherapy with nivolumab and ipilimumab for locally advanced clear cell renal cancer resulted in a complete response of an extensive vena cava tumor thrombus, which enabled curative-intent resection of a non-responding primary tumor. If validated in larger cohorts, preoperative immunotherapy for locally advanced renal cell carcinoma may ultimately impact surgical planning and long-term prognosis.